Desain UI dan UX pada Aplikasi Android Coronavirus Disease 2019 (COVID-19) - Viving Frendiana; Dandun Widhiantoro (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2020)
Coronavirus infection is a disease caused by the corona virus and causes symptoms in the form of respiratory problems. This virus was first discovered at the end of 2019 in the city of Wuhan, China and until the end of 2020 it has spread to almost all over the world. To reduce the spread of the coronavirus, healthy habits such as washing hands and wearing masks are needed. In addition, in terms of technology, Android is an operating system that is widely used to develop mobile applications. The existence of this application technology makes it very possible to use it to update the latest information about COVID-19, as well as prevent the spread and the tracking process. The UI UX design is needed in making the 2019 coronavirus disease (COVID-19) android application. Based on the results of testing the functional suitability aspect has a success percentage of 100%. And the results of the calculation of the percentage of feasibility is 95.66%, so it can be concluded that the application has a very decent usability standard. Keywords— COVID-19, Coronavirus, Android, UI UX, Android Studio